2021
DOI: 10.1037/bul0000313
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effects of time perspective: A meta-analysis testing a self-regulatory framework.

Abstract: This is a repository copy of Understanding the effects of time perspective : a meta-analysis testing a self-regulatory framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 119 publications
(220 reference statements)
3
70
0
3
Order By: Relevance
“…When necessary, we changed the direction of correlation coefficient to ensure that each effect size reflected the relation between higher levels of affect and higher consumption volume. The standard error for each effect size was calculated using the following formula: SE( r ) = √1- r 2 / N -2 (following [ 68 ]), while the variance was obtained by squaring the standard error.…”
Section: Methodsmentioning
confidence: 99%
“…When necessary, we changed the direction of correlation coefficient to ensure that each effect size reflected the relation between higher levels of affect and higher consumption volume. The standard error for each effect size was calculated using the following formula: SE( r ) = √1- r 2 / N -2 (following [ 68 ]), while the variance was obtained by squaring the standard error.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, low selfcontrol and orientation toward the present may be related to higher distress, substance use and risky behaviors (Daugherty and Brase, 2010;Dwivedi and Rastogi, 2017). Thus, it can be assumed that two groups of variables might be especially relevant for self-control processes, including coping styles: time perspectives (TPs) (Baird et al, 2020;Mucha et al, 2020) and impulsivity dimensions (IDs) (Li et al, 2019;Nigg, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Depressive symptoms are negatively related to psychological capital (Han et al, 2019). A systematic search found that a future time perspective had small-to-medium-sized positive associations with goal setting, self-regulatory ability, and outcome (Baird et al, 2021). Meanwhile, psychological capital was positively related to outcome and self-regulatory ability.…”
Section: Studymentioning
confidence: 99%